(untitled) (Journal of Misan Researches, 2025)
Abu Muslim al- Khorasani and his role in the establishment of the Abbasid State has had a profound impact on the emergence of the Abbasid State since it was a secret call and the important role he played in the support of this call, especially in Persia, specifically in Khorasan. The Second Abbasid Caliph Abi Jafar Al-Mansour has another view on limiting the persistence of an Abu Muslim in the main role entrusted to him. Abu Muslimi al-Khorasani is one of the main pillars of the clandestine and public Abbasid advocacy so that he took over the leadership of the clandestine organization of the call and became a major and important project, namely the overthrow of the and the establishment of the Abbasid States. "The satisfaction of the Muhammad", Abu Jafar al-Mansour managed to get rid of him and end an important era for the Abbasid State after having made many contributions to the establishment of this State.